Comprehensive evaluation of the Ruoergai Prairie ecosystem upstream of the Yellow River - Xu, Xiangning; Yang, Qingwen; Xiang, Guoping; Liu, Tao; Yang, Mengjie; Xiong, Xi; Jiang, Tao (Frontiers in Ecology and Evolution, 2023)
With complex and diverse ecosystem types and complete ecological elements like mountain, river, forest, farmland, lake, grassland, sand and glacier, Ruoergai Prairie upstream of Yellow River is not only an important part of the Qinghai-Tibet Ecological Barrier but also the key area for ensuring ecological security of China. Due to the influence of climate change and artificial activity, Ruoergai Prairie has the problems of grassland degradation, water and soil loss and forest area reduction, and ecological restoration is needed. So making a comprehensive ecosystem evaluation is of great guiding significance for its ecosystem restoration. This paper evaluates the ecosystem quality, ecosystem service function importance, ecological vulnerability, ecological protection importance, ecological resilience and ecological landscape pattern of prairie, wetland and forest. The results show that the ecological landscape in the study area is heavily degraded. Protection and restoration of mountains, waters, forests, farmlands, lakes, grasslands, sand and glacier are needed.